Mbira of the Ndau - Tracey, Andrew (International Library of African Music, 2022)
The article, arising from research done in 1972, follows on the author’s series of analyses of the instrumental music of the Shona and Sena peoples of the Zambezi Valley. The analyses in this article focus on the relatively unknown mbira of the Ndau. The article describes its hexatonic note layout, highly variable tunings, and its variations among the Ndau-and Shangana-speaking groups in Southeast Zimbabwe and adjacent regions of Mozambique and South Africa. It includes the historical effect of the Shangana invasion of the nineteenth century into Mozambique. The article further discusses the transcription of the mbira’s music, in staff or the author’s own tablature, with detailed description of the latter. It compares Ndau with Shona concepts of ownership of songs, the practice of kubempa as used by Ndau travelling musicians and the difficulties of working in pre-independence Mozambique. The article presents songs in tablature, some by Bonisa Sithole, the author’s field assistant.
Keywords: Mbira; Mbira music; Shona (African people); Ndau (African people); Tsonga (African people); Musical instruments; Transcription; Musical Tuning; Zimbabwe; Hexatonic Scale; Mozambique; Mbira dzaVaNdau (Instrument); African Music; Mbira (Instrument)